A Multi-Functional Grid-Tied PV System Using a Split Source Inverter With Energy Management and Power Quality Improvement Features - Abbes Kihal (16904694) (2025)
In this paper, split-source inverter (SSI) is proposed for multi-functional grid-connected (MFGC) application because it offers the better boosting capability with fewer components. Furthermore, the SSI could operate as a full active power filter (APF), unlike the impedance source inverter (ZSIs) topologies. This paper proposes a sliding mode control (SMC) scheme for controlling both DC and AC sides of the MFGC system based SSI, the MFGC system aims to compensate the reactive power at grid side, satisfy the non-linear load power demand using the extracted PV power, and inject the remaining PV power into the grid. On DC-side, the SMC scheme is designed to control the DC input current while estimating the duty cycle that ensures the boosting capability. Then, a decoupled control scheme based on the SMC is designed to control the AC-side of the system and estimate the reference voltages that are fed to a modified space vector modulation (MSVM) stage. The entire system is simulated using the MATLAB/Simulink environment and validated experimentally through real-time hardware in the loop setup. The obtained results from simulation and HIL setup demonstrate the effectiveness and robustness of the proposed control scheme in terms of power management and power quality enhancement. Other Information Published in: IEEE Access License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1109/access.2025.3538069